Investigation of Changes in Soil Erodibility Using the USLE Model and Determination of Effective Factors (Case Study: Dorahan Watershed-Borujen City) - J. Karimi Shiasi; F. Fotouhi Firoozabad; A. Fathzadeh; M. Hayatzadeh; M. Shirmardi (علوم آب و خاک)
One of the main factors contributing to water erosion is the inherent characteristic of soil erodibility. Erodibility depends on particle size distribution, organic matter, structure, and soil permeability. This research aimed to investigate changes in the soil erodibility factor across geomorphological facies. The soil erodibility index was estimated by sampling 58 points within the geomorphological facies of the Dorahan watershed, using the Wischmeyer and Smith method. In the laboratory, soil granularity distribution, organic matter, soil structure, the amount of gravel, lime, salinity, acidity, and sodium absorption ratio were measured. Results indicated that soil erodibility across the entire area ranges from 0.0148 to 0.0661 (t.hr/Mj.mm). The soil erodibility index (K) for the hro-p1 and hro-p2 facies is higher than for others and exhibits the widest range of variations compared to the other facies. The lowest range of changes within geomorphological facies is associated with the hrc facies. The erodibility index decreases from the east to the west of the basin due to the presence of exposed rock faces, which protect the soil as a cover layer.